Carte de l'Isle de Terre-Neuve - Bellin, Jacques Nicolas, 1703-1772 ([Paris], 1744)
Black and white. Prime meridian Paris. Depths indicated by soundings. Two bar scales: French common leagues, and French and English marine leagues. Includes note describing the island as uncharted territory. CNS map no. 30.